ANALYSIS OF THE ETIOLOGICAL STRUCTURE AND ANTIBIOTIC SENSITIVITY OF INFECTIOUS AGENTS ASSOCIATED WITH MEDICAL CARE IN SURGICAL HOSPITALS - Ольга Николаевна Воробьева; Светлана Александровна Дулепо; Татьяна Геннадьевна Несвет; Наталья Михайловна Жилина (Медицина в Кузбассе)
Knowledge of the structure of wound and SMP pathogens and regular monitoring of the dynamics of their resistance to antimicrobial drugs makes it possible to effectively combat purulent-inflammatory complications, optimize empirical and etiotropic therapy.